Efficacy of local tranexamic acid treatment for prevention of bleeding after dental procedures: A systematic review and meta-analysis - Duangrat Owattanapanich; Patompong Ungprasert; Weerapat Owattanapanich (Elsevier, 2019)
Background/purpose: Tranexamic acid (TA) is one of the commonly used local hemostatic agents for dental procedures and a previous study has demonstrated a significantly lower incidence of post-procedural bleeding (PPB) in patients taking warfarin and received local TA treatment after the dental procedures than those who took warfarin and did not receive local TA treatment. However, it is still unknown whether post-procedural local TA treatment can lower the bleeding risk to the same level as individuals who do not take oral anticoagulant (OAC). The current study aimed to compare the PPB risk in patients who took OAC and received local TA treatment after the dental procedures and individuals who did not take OAC and underwent similar dental procedures. Materials and methods: We systematically searched primary researches from two databases and four eligible cohort studies were identified. The bleeding incidence was collected from each study and the pooled odds ratio (OR) and 95% confidence interval (CI) of PPB were calculated using Mantel-Haenzel method. Results: The analysis revealed a higher risk of PPB in patients who took OAC and received local TA treatment after the dental procedures than individuals who did not take OAC and underwent similar dental procedures with the pooled OR of 2.4, although the pooled effect estimate had a relatively wide 95% CI with non-statistically difference (0.69-8.12). Conclusion: This study results serve as a reminder to dentists that the increased risk of PPB in those who took OAC is not entirely resolved by the local TA treatment. Keywords: Anticoagulants, Bleeding, Dental procedure, Tranexamic acid, Warfarin